Freshwater fishes of Universiti Malaysia Kelantan, Jeli Campus: a preliminary checklist (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
The fish fauna was surveyed in Sungai Buloh and Sungai Lachang which flow through the Universiti Malaysia Kelantan (UMK) Jeli Campus area. Both rivers are tributaries of the Sungai Golok drainage, which runs through Kelantan state and serves as a major border between Malaysia and Thailand. The objectives of this study were to document fish species checklist distribution within Universiti Malaysia Kelantan Jeli Campus and accessed the status of freshwater fishes, according to the IUCN Red List of Threatened Species. The fish sampling was conducted in February and May 2022 in two sampling point inside UMK Jeli Campus area. During the survey period, 40 native species from 18 different families were identified and documented.  Family Cyprinidae recorded the highest number of total species with 25% of total species followed by family Danionidae, 10% and family Balitoridae, 10%.  The introduced species, Oreochromis niloticus, was not observed during the survey, despite the fact that the species is commonly used for aquaculture activities on campus.Keywords: Fish, fauna, river, freshwater, checklist
Keywords: Fish; fauna; river; freshwater; checklist